2017
DOI: 10.1136/bmjopen-2017-018107
|View full text |Cite
|
Sign up to set email alerts
|

Single-centre retrospective analysis of growth hormone supplementation in IVF patients classified as poor-prognosis

Abstract: BackgroundPatients undergoing in vitro fertilisation (IVF) receive various adjuvant therapies in order to enhance success rates, but the true benefit is actively debated. Growth hormone (GH) supplementation was assessed in poor-prognosis women undergoing fresh IVF transfer cycles.MethodsData were retrospectively analysed from 400 IVF cycles, where 161 women received GH and 239 did not.ResultsClinical pregnancy, live birth rates and corresponding ORs and CIs were significantly greater with GH, despite patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 25 publications
10
51
0
Order By: Relevance
“…This may mean that alternative, weaker studies, such as retrospective cohort studies, may be required to advance the field provided they are stringently designed, conducted and analysed. Two recent retrospective studies by our group showed that CP and LB rates were significantly greater with GH (3.42-fold and 6.16-fold higher, respectively) following the transfer of fresh autologous embryos in stimulated cycles [12,13]. Age at embryo transfer (ET) and morphological quality of the transferred embryo were the only other significant independent predictors of the likelihood of CP and LB, but no significant differences were observed in the proportion of high-quality embryos generated in the GH arm, echoing the most recent prospective study [8].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…This may mean that alternative, weaker studies, such as retrospective cohort studies, may be required to advance the field provided they are stringently designed, conducted and analysed. Two recent retrospective studies by our group showed that CP and LB rates were significantly greater with GH (3.42-fold and 6.16-fold higher, respectively) following the transfer of fresh autologous embryos in stimulated cycles [12,13]. Age at embryo transfer (ET) and morphological quality of the transferred embryo were the only other significant independent predictors of the likelihood of CP and LB, but no significant differences were observed in the proportion of high-quality embryos generated in the GH arm, echoing the most recent prospective study [8].…”
Section: Introductionmentioning
confidence: 76%
“…Nonetheless, these classifications have not been able to define subsets of poor-prognosis patients who can benefit from various ART interventions including adjuvant co-treatment [31]. In our previous studies, we introduced the concept of reduced embryo quality as an additional diagnostic parameter for poor-prognosis patients, whereby those with > 50% of embryos with marked fragmentation are predicted to have poorer outcomes [1,12,13]. In the current study, we used the same criteria to define a poor prognosis, and it is these patients who are offered adjuvant therapies such as GH in order to enhance their primary ART outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent retrospective study including 400 women in which 161 had been treated with GH (average of 1.5 IU per day), Keane et al (16), reported that GH supplementation significantly increased clinical pregnancy rate by 3.42-fold (95% CI 1.82 to 6.44, p<0.0005) and live birth rate by 6.16-fold (95% CI 2.83 to 13.39 p<0.0005) (16). When the data were analyzed based on female age, the authors noticed that the effect of GH was mainly related to patient's age.…”
Section: Growth Hormone (Gh) Supplementationmentioning
confidence: 99%